Growth, nodulation, and anatomical characterization of Calopogonium mucunoides Desv., a tropical legume, in copper-contaminated soil - Ferreira, Tassia Caroline [UNESP]; Rosalem, Patrícia Fernanda [UNESP]; Aguilar, Jailson Vieira [UNESP]; da Silva, Victor Navarro [UNESP]; de Araujo, Maycon Anderson [UNESP]; Martins, Aline Redondo [UNESP]; de Camargos, Liliane Santos [UNESP] (Springer Nature, 2023)
Copper is an essential plant micronutrient, vital in physiological processes. However, excessive copper concentrations can lead to toxicity, adversely impacting biomass accumulation. This study aimed to investigate the effects of toxic copper doses on establishing Rhizobium nodulation, biomass accumulation capacity, and anatomical changes in leaves and roots of Calopogonium mucunoides plants. The hypothesis was that C. mucunoides plants could sustain growth even under toxic copper doses and exhibit anatomical alterations after 45 days of cultivation. Soil contamination was conducted using copper sulfate at various doses: 0 (control), 30, 60, 120, 240, and 480 mg dm−3. Root, nodule, and shoot dry mass values were obtained by drying and weighing the plants after 72 h. For anatomical analysis, samples were fixed in 70% FAA, dehydrated using an ethyl series, and embedded in historesin. Slides were stained with toluidine blue, and histochemical tests were performed. No anatomical changes were observed in the leaves across all analyzed tissues. However, in the roots, a decrease in xylem and secondary phloem thickness was observed at the dose of 30 mg dm−3, while an increase in vessel element thickness was observed at the doses of 60 and 120 mg dm−3. Histochemical tests revealed the presence of compounds such as starch and pectins in both leaves and roots, as well as lipids at the base of the tector trichomes in the leaves. C. mucunoides demonstrated the ability to maintain growth and nodulation at concentrations of up to 120 mg dm−3 of copper in the soil, with impaired growth observed at higher doses.
Keywords: Abiotic stress; Biomass accumulation; Heavy metals; Morphophysiological changes